Mixed Land Use and its Effect in Integration of the Residential Neighborhood (Journal of University of Babylon for Engineering Sciences, 2019)
Mixed use is one of the principles used in the development to solve problems of zoning and its negative effects in urban environments, which have been diagnosed with loss of vitality and integration. The research defines mixed use as the integration of a range of activities and functions of urban land uses within the residential area within different dimensions and spatial levels in order to achieve integration that supports the vitality and diversity of the place. The main problem of research was that "there is no clear perception of the role of mixed use in the integration of the residential neighborhood.". The objective of the research is to built a comprehensive theoretical framework that includes the vocabulary and values of the integration of the residential neighborhood. The research hypothesis was that mixed use plays a role in the integration of the residential neighborhood. The research followed the analytical method. The theoretical framework was applied on one of Baghdad's neighborhoods, namely Al-Saydia district, which was planned according to the development plans of the polservice housing policy . In order to test the research hypothesis, the research adopted three methods of measurement (syntactic analysis, mathematical equation, questionnaire form).The research findings was that mixed use plays a role in achieving urban integration through the urban nuclei and its location, and achieving functional integration through the feature of urban fabric diversity, and the vitality of the public realm, and finally achieving the physical integration through the feature of centrality and spatial differentiation of the fabric, as well as accessibility.